Measurement of differential cross sections and charge ratios for t-channel single top quark production in proton-proton collisions at √s=13 TeV; European Physical Journal C; Vol. 80, iss. 5 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen